Adjacent-Compensation Consensus Algorithm in Asynchronously Coupled Form for Second-Order Multiagent Network under Communication Delay. (20th February 2014) - Liu, Cheng-Lin; Liu, Fei
Abstract : General asynchronously coupled consensus algorithm associated with adjacent compensations, is proposed to solve the dynamical consensus problem of second-order multiagent network with communication delay under leader-following coordination control framework. Based on frequency-domain analysis, firstly, delay-independent consensus convergence is proved for the second-order multiagent systems with a spanning tree topology that has the leader root and then delay-dependent consensus condition is obtained for the multiagent systems with communication delay under a general leader-following interconnection topology. Simulation illustrates the correctness of the results.